2012
DOI: 10.1039/c2sm25526j
|View full text |Cite
|
Sign up to set email alerts
|

Probing the dynamics of particles in an aging dispersion using diffusing wave spectroscopy

Abstract: International audienceWe have studied theoretically and experimentally the dynamic multiple light scattering properties of a liquid dispersion (an aqueous foam for the experiments) having a continuous phase doped with colloidal scatterers (monodisperse latex beads for the experiments). The temporal auto-correlation function of the scattering intensity shows two characteristic timescales. The slow timescale is related to the reorganization of the dispersion induced by aging, while the fast timescale is related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This strongly suggests that this decay is indeed due to the motion of a small fraction of single particles that are not yet part of the network. The decreasing magnitude of the intermediate decay with sample age indicates that the number of these mobile particles is a decreasing function of the age of the sample [51,52]. We can thus conclude that the temporal .…”
Section: Dynamical Characteristicsmentioning
confidence: 69%
“…This strongly suggests that this decay is indeed due to the motion of a small fraction of single particles that are not yet part of the network. The decreasing magnitude of the intermediate decay with sample age indicates that the number of these mobile particles is a decreasing function of the age of the sample [51,52]. We can thus conclude that the temporal .…”
Section: Dynamical Characteristicsmentioning
confidence: 69%
“…DWS analysis of the coarsening of an aqueous foam loaded with monodisperse latex beads revealed that the temporal autocorrelation function of the scattering intensity presents two decays decoupled and separated in time. These distinct decays are due to two different processes: bubble rearrangements during foam ageing, which is responsible for the longer decay, and Brownian motion of the colloidal particles in the liquid fraction, giving rise to the shorter decay [121].…”
Section: Spectral Studies Of Foamsmentioning
confidence: 99%
“…The other mechanism is due to gradients of pressure, between inner and outer of the bubble, driving the gas from smaller bubbles to greater bubbles [1,2]. Several experimental techniques and theoretical models have been proposed exploring the properties and complex dynamics of foams, which have some aspect of physical chemist that are unclear and motivate new procedures to understand the dynamics of this material [3,4].…”
Section: Introductionmentioning
confidence: 98%